XÁC ĐỊNH NHÓM HIDROCACBON THƠM BTEX TRONG NƯỚC VÀ KHÔNG KHÍ BẰNG PHƯƠNG PHÁP SẮC KÍ KHÍ KẾT HỢP VỚI KĨ THUẬT VI CHIẾT PHA RẮN MÀNG KIM RỖNG PHỦ TRONG - Huệ, Nguyễn Đức; Trí, Trần Mạnh; Huy, Đỗ Quang; Đoàn, Đặng Văn (Vietnam Journal of Science and Technology, 2012)
DETERMINATION OF THE BTEX GROUP AROMATIC HYDROCACBONS IN WATER AND IN AIR BY GC METHOD USING SOLID-PHASE DYNAMIC MICROEXTRACTION (SPDME) Solid-phase dynamic microextraction (SPDME) is a modified method of fiber solid-phase microextraction (SPME). The method involves the sorption of analytes onto a thin film of stationary phase, which is coated on inner surface of a syringe needle followed by desorption of analytes from a sample into a chromatographie injector for analysis. A great advantage of SPDME over fiber of SPME, the SPDME is impossible to damage mechanically. In addition, the volume of the stationary phase of SPDME needle is larger than that of SPME fiber many times. Relying on that, we can increase the amount of analyte and sensitivity of analytical method. The study on SPDME technique based on SPME is a new modification and contribution to improve sample preparation technique for chromatographic analysis. In this report, we present to make device for SPDME based on stationary phase of polymethylphenylsiloxane (OV-17) and veterinary syringe and study on the method of SPDME combined with the GC/FID and GC/MS for determination of the BTEX group aromatic hydrocacbons in water and in air.